AN INVESTIGATION ON THE IMPACT OF POLYVINYL CHLORIDE (PVC) ON THE BEHAVIOUR OF BITUMINOUS CONCRETE MIX (International Journal of Food and Nutritional Sciences, 2021)
Waste PVC that has been used previously as mineral water bottles, pipes, electrical fittings etc. are biologically non-degradable and posed an ominous environmental problem which led to severe environmental impact. But molten PVC has a binding property which can be reused with bitumen to reduce the cost of bituminous mix. At the same time the recycling of waste PVC save disposal sites and to reduce the amount of inert drawn from quarries, which often lead to environmental problems. This paper describes the investigation of the properties of bitumen mixed with PVC (2.5%, 5%, 7.5%, 10%, 12.5%, 15%, 17.5% and 20% by the weight of bitumen) at optimum bitumen content and to check the design criteria of bituminous mixes using this bitumen-PVC binder. The investigation concentrated on the test of strength properties of coarse aggregates and Marshall Design properties of bituminous mixes according to the test procedure specified by AASHTO. Some of the measured properties of bituminous mix with bitumen-PVC binder used in this study were within the acceptable recommended limits. On the basis of experimental results of this investigation, it is concluded that the dense graded bituminous mixes with bitumen containing PVC up to 10% can be used for bituminous pavement construction in warmer region from the stand point of stability, stiffness and voids characteristics